Board Gender Diversity, Corporate Social Responsibility Disclosure, and Firm’s Green Innovation Performance: Evidence From China - Naveed, Khwaja; Voinea, Cosmina L.; Roijakkers, Nadine (Frontiers in Psychology, 2022)
The current research investigates the interplay of board gender diversity (BGD), the quality of Corporate Social Responsibility Disclosure (CSRD) and the firm’s Green Innovation performance (GIP). It examines the moderation effect of CSRD on the relationship between corporate GIP and BGD. The study inculcates 3,736 firm-year observations of A-share listed Chinese firms from 2010 to 2019. The least-square dummy variable, Generalized methods of moments and 2SLS are employed for the analysis of the study. The findings foster an affirmative and significant impact of BGD on corporate GIP in terms of Green Innovation patents. Moreover, the quality of CSRD is also detected for a significant moderating effect on the relationship between BGD and corporate GIP. The quality of CSRD comes out to be an indicator of the social resilience and female role congruence under the purview of social resilience theory and role congruence theory respectively. This research would help managers and policymakers of developing nations in formulating the environmental innovation strategies for corporate sustainability.